Intensification of 2′-Fucosyllactose biosynthesis pathway by using a novel fucosyltransferase from Bacillus cereus - Zhang, Kainuo; Gao, Miaomiao; Cao, Chenqi; Zhang, Mengxin; Ahmad, Waqar; Rady, Ahmed; Aldahmash, Badr; Zhu, Tianze; Khan, Shahin Shah; Liu, Luo (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction2′-Fucosyllactose (2′-FL) is an oligosaccharide that can be synthesized in the human body and is known for its health-promoting and prebiotic effects. The biosynthesis of 2′-FL using microorganisms has received attention recently due to its increased application in nutritional and medical infant formulations.MethodsThis work attempts the new application of Bacillus cereus α-1,2-fucosyltransferase (FutCB) in the de novo synthesis of 2′-FL in Escherichia coli (E. coli). Additionally, knocking out the LacZ and WaaF genes alongside overexpression of the key gmd, manB, wcaG, and manC genes enhances the availability of the necessary precursors GDP-L-fucose and lactose for the synthesis of 2′-FL.Results and discussionThe use of constitutive promoters achieved better control over the production of 2′-FL during fed-batch fermentation. After 64 h of fermentation, the modified E. coli strains produced 121.4 g/L 2′-FL with a yield of 1.90 g/L/h, resulting in an impressive 2′-FL output. These results together indicate the potential of large-scale, high-yield production of 2′-FL and form a basis of much more refinement to be done. The next step will focus on maximum substrate utilization, alteration of gene regulation, and improvement of commercial-scale synthesis.